Uso de frutos y follaje arbóreo en la alimentación de vacunos en la época seca en Boaco, Nicaragua - Ibrahim, Muhammad Akbar; Zamora, Sheyla; García, Jeymi; Bonilla, Glenda; Aguilar, Holmes; Harvey, Celia A. (CATIE, Turrialba (Costa Rica), 2015)
5 ilus. 6 tab. 6 ref.